Persepsi Guru kelas IV SD AL FURQON Lubuklinggau terhadap pendidikan karakter dalam kurikulum 2013 dan implementasinya - Mas Agung Tri Putro; Puspa Djuwita; Bambang Parmadi (UNIB Press, 2024)
In order to achieve character education through C-13, teachers need to instill character education values ​​contained in K-13 through learning to strengthen character so that students not only master the learning material but have the desired character in K-13. The purpose of this study was to find out how the fourth grade teacher at SD Al Furqon Lubuklinggau felt about character education and its implementation in that class, especially at KI 1 and KI 2. This study used a qualitative research method with a case study approach. The case in the research that has been carried out by researchers is about how the fourth grade teacher at Al Furqon Elementary School perceives character education and also its implementation. Meanwhile, the number of subjects in the study amounted to 4 teachers. For research instruments, researchers used interview and observations The results of the study found that the teacher had a positive perception of character education in the K 13 curriculum that was implemented in the SD, this was because the teacher gave good views and responses and also supported the application of character education in interviews that had been conducted through three perception indicators. the. Meanwhile, in its implementation, the character values ​​that are implemented are religious values ​​on KI 1, character values ​​of honesty, discipline, responsibility, caring, confidence, courtesy and discipline on KI 2. From the implementation process, the teacher is in accordance with what was planned.